Legal Protection for Persons with Disabilities: International Law and Implementation in Padang - Rosra, Deswita; Palupi, Dwi Astuti; Suamperi, Suamperi; Annisa, Febrina (Faculty of Law, Andalas University, 2024)
This research explores the protection of the rights of persons with disabilities in Padang City, West Sumatra, Indonesia, in light of the legal framework and local government initiatives aimed at promoting inclusivity and empowerment. Despite national and international legal commitments, such as Indonesia’s ratification of the Convention on the Rights of Persons with Disabilities (CRPD) and the enactment of Law No. 8 of 2016 on Persons with Disabilities, the protection of persons with disabilities remains inadequate in practice. This study examines the efforts of the Padang City Government, which has been proactive in implementing various measures to address the needs of persons with disabilities, including the designation of Disability-Friendly Zones and the provision of accessibility infrastructure. However, challenges persist, particularly regarding social protection and economic inclusion. Using a qualitative social science approach, the research analyzes the legal protection model for persons with disabilities in Padang City, focusing on the implementation of Regional Regulation No. 3 of 2015. The findings highlight the importance of integrated social protection systems, gradual implementation of accessibility measures, and the need for a collaborative approach involving local governments, the private sector, and communities to fully realize the rights and welfare of persons with disabilities. This study suggests a legal protection model that combines social protection, capacity building, and enhanced accessibility to improve the dignity and independence of persons with disabilities in Padang City.